2017
DOI: 10.1186/s13065-017-0341-x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antiproliferative activity of blue corn and tortilla from native maize

Abstract: BackgroundBlue corn is a cereal rich in phenolic compounds used to make blue tortillas. Tortillas are an important part of the Mexican diet. Blue corn and tortilla represent an important source of the natural antioxidants anthocyanins. However, studies on their biological activity on cancer cell lines are limited. The goal of this study was to evaluate the antioxidant and antiproliferative activity of blue corn and tortilla on different cancer cell lines.MethodsTotal polyphenol content, monomeric anthocyanins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 24 publications
1
26
0
7
Order By: Relevance
“…Epidemiological studies have demonstrated a relationship between the consumption of food with high quantities of phenolic compounds and a reduction in the risks of chronic and degenerative diseases, such as cancers and cardiovascular disease. Corn seed possesses antidiabetic, antioxidant, antiproliferative, and anti-cataractogenic activities [18,[39][40][41].…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Epidemiological studies have demonstrated a relationship between the consumption of food with high quantities of phenolic compounds and a reduction in the risks of chronic and degenerative diseases, such as cancers and cardiovascular disease. Corn seed possesses antidiabetic, antioxidant, antiproliferative, and anti-cataractogenic activities [18,[39][40][41].…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The diverse pigmentation of corn is due to the presence of phytochemicals such as carotenoids [1] and anthocyanins, a class of phlobaphene pigment [2]. Purple corn, in particular, is rich in anthocyanins and related traits such as total phenolic compound and antioxidant activity [3][4][5], and accumulation of high value compounds such as anthocyanins in specific tissues makes it possible to develop production strategies for high value chemicals using these tissues as feedstock. Anthocyanin is a natural purple pigment and an antioxidant agent [4] with human health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Purple corn, in particular, is rich in anthocyanins and related traits such as total phenolic compound and antioxidant activity [3][4][5], and accumulation of high value compounds such as anthocyanins in specific tissues makes it possible to develop production strategies for high value chemicals using these tissues as feedstock. Anthocyanin is a natural purple pigment and an antioxidant agent [4] with human health benefits. For instance, it reduces the risk of chronic diseases such as cancer [6] and obesity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, both extracts reduced the TBARS production in homogenized rat brains (IC 50 = 792 mg/mL and IC 50 = 750 mg/mL, respectively). These fi ndings suggest that the nixtamalization process improves the biological anthocyanin's properties [Herrera-Sotero et al, 2017]. Finally, these results show also that the antioxidant activity of anthocyanins depends on the type, number, and glycosylation site in the molecule of anthocyanidins contained in the maize kernel as well as methodology used to evaluate the antioxidant capacity of these compounds [Zhao et al, 2014].…”
Section: Antioxidant Capacity Of Anthocyaninsmentioning
confidence: 73%